(untitled) (LEGAL DIALOGICA, 2025)
The purpose of this research is to understand the legal regulation of personal guarantees as collateral and to comprehend the legal responsibilities of personal guarantors in the case of non-performing loans. This research applies a normative legal method, which involves examining existing legal rules and principles to resolve legal issues. The sources used as references include laws and regulations, legal theories, and written legal doctrines. Based on the research findings, the regulation of personal guarantees in the Indonesian Civil Code (Articles 1820–1850) remains general in nature and does not provide adequate legal protection for guarantors, particularly in the context of modern banking and complex business transactions. There is a legal vacuum and ambiguity regarding the extent of a guarantor’s liability, how legal privileges are exercised and waived, and the protection of guarantors who may not fully understand the risks they are assuming. A personal guarantee has an accessory legal nature, meaning it only becomes effective if the principal debtor defaults. However, in practice, guarantors often forgo their legal privileges and consequently bear liabilities directly, without waiting for the enforcement of the debtor’s assets. It is recommended that reforms and harmonization of regulations regarding personal guarantees are necessary, especially in clarifying the limits of guarantor liability, mechanisms for waiving legal privileges, and legal protection for guarantors in credit agreements. It is also important to align the provisions of the Civil Code with bankruptcy and debt restructuring (PKPU) regulations so that the scope and responsibilities of guarantors can be more clearly defined, including legal protections for the heirs of guarantors. Abstrak: Tujuan Penelitian ini adalah untuk mengetahui pengaturan hukum personal guarantee sebagai objek jaminan serta untuk mengetahui dan memahami tanggung jawab hukum personal guarantee terhadap kredit bermasalah. Penelitian ini menerapkan metode hukum normatif, yakni pendekatan yang menelaah aturan dan prinsip hukum yang ada untuk menyelesaikan persoalan hukum. Sumber-sumber yang dijadikan acuan meliputi undang-undang, teori hukum, dan doktrin hukum tertulis. Berdasarkan hasil penelitian Pengaturan hukum personal guarantee dalam KUHPerdata (Pasal 1820–1850) masih bersifat umum dan belum memberikan perlindungan hukum yang memadai bagi penjamin, khususnya dalam konteks perbankan modern dan transaksi bisnis yang kompleks. Ditemukan adanya kekosongan hukum serta ketidakjelasan norma terkait sejauh mana tanggung jawab penjamin, bagaimana hak istimewa dijalankan dan dilepaskan, serta perlindungan terhadap penjamin yang tidak sepenuhnya memahami risiko yang ditanggung. Personal guarantee memiliki sifat hukum yang bersifat accessoir, artinya hanya berlaku jika debitur utama melakukan wanprestasi. Namun, dalam praktiknya, penjamin kerap kali mengesampingkan hak istimewanya, sehingga harus menanggung kewajiban secara langsung tanpa menunggu pelaksanaan eksekusi terhadap aset debitur terlebih dahulu. Saran diperlukan pembaruan dan harmonisasi aturan mengenai personal guarantee, terutama dalam memperjelas batas tanggung jawab penjamin, mekanisme pelepasan hak istimewa, serta perlindungan hukum bagi penjamin dalam kontrak kredit. Penting juga untuk menyelaraskan ketentuan dalam KUH Perdata dengan regulasi kepailitan dan PKPU agar ruang lingkup dan tanggung jawab penjamin dapat ditetapkan dengan lebih tegas, termasuk perlindungan hukum bagi ahli waris penjamin.